VD_FINDINFO HC / 2016 / 130 vom 8. Februar 2016 - VD Tribunal cantonal (2016)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS, RADIATION DU RÔLE | 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)